Organic Nutrient Solutions for Hydrophonic Spinach (Basella alba) Production in Urban Agriculture - Dhananjani, B.A.; Pakeerathan, K. (Faculty of Agriculture, Sabragamuwa University of Sri Lanka, 2023)
Purpose: Macro and micronutrients rich vegetable and fish wastes are generated hugely in Sri Lanka, but not recycled properly into valuable byproducts. It is a serious problem and needs to be managed to make environment free from pollution. Extraction of nutrients from organic wastes can be used as liquid fertilizers for hydroponic crop production even in congested urban cities. Research Method: Organic hydroponic medium using vegetable waste extracts (M2), fish emulsion (M3), vermi tea (M4), the mixture of M2+M3+M4, and Albert’s solution (M1-control) were prepared and tested on Spinach. The experimental setup was arranged in a CRD with four replicates. The nutritional qualities of formulated liquid fertilizers (N, P, K, Ca, Na), pH, EC, spinach growth parameters such as plant height, number of leaves per plant, leaf area, root length, weight (Fresh /Dry) were measured eight weeks after planting and subjected to ANOVA using SAS 9.1. Tukey’s HSD multiple comparison test to identify the best treatment combination at P <0.05. Findings: The results revealed that the amount of each N, P, K, Na, and Ca was significantly different between treatments (P <0.05). The highest quantity of each N (11.1mg/L), P (37.99mg/L), and K (145,5 mmol/L) was detected in M2. Whereas, Na and Ca quantities were highly significant in M4 with the values of 208.7 and 96.2 mmol/L, respectively. Plant height and root length in M1, M2 and M3 were significantly higher than those of other treatments. Fresh and dry weights were also significantly higher in M3, M1 and M2 treatments when compared with other treatments. The highest leaf number and leaf area were also recorded in M3 treatment after 8 weeks of planting. Originality/ Value: This study shows that fish emulsion solution is found to be more promising and both fish emulsion and vegetable waste hydrophonics medium can be used as alternatives to Albert’s solution
Keywords: Basella alba; Fish emulsion; Hydroponics; Liquid organic fertilizer; Vegetable waste